THE EFFECT OF WORK SAFETY AND HEALTH, TRANSFORMATIONAL LEADERSHIP, AND ORGANISATIONAL CULTURE ON THE ORGANISATIONAL COMMITMENT OF EMPLOYEES OF MATARAM FISH QUARANTINE, HARVESTING AND FISH QUALITY CONTROL CLASS II - Milis Milis (Master of Management, Mataram University, 2016)
This research is aimed at determining the effect of work safety and health transformational leadership and organisational culture on the organisational commitment and at analysing which variable is the most dominant to affect the organisational commitment of employees of Mataram Fish Quarantine, Harvesting and Quality Control (FQHQC) Class II. This research is associative-causal research where the data were collected from 57 employees of FQHQC Class II Mataram through quetionnaires. The data were analysed using Multiple Linear Regression Analysis, and the hypothesis was tested partially and simultaneously. The research showed that work safety and health, transformational leadership and organisation culture partially and simultaneously have significant effect on the organisational commitment employees of FQHQC Class II Mataram. The variable of transformational leadership is the most dominant factor to affect the organisational commitment of employees of BKIPM Class II Mataram. The research concluded that work safety and health, transformational leadership and organisational culture have significant effect on the organisational commitment of employees of BKIPM Class II Mataram. The variable of transformational leadership is the most dominat factor to affect the organisational of employees of BKIPM Class II Mataram. The transformatonal leadership style applied in FQHQC Class II Mataram should prioritize the improvement of work safety and health, organisational culture of employees to improve the organisational commitment of employees of FQHQC Class II Mataram. Keywords: Work Safety and Health, Transformational Leadership, Organisation Culture, and Organisational Commitment.